SOCS3 Negatively Regulates Cardiac Hypertrophy via Targeting GRP78-Mediated ER Stress During Pressure Overload - Liu, Shuang; Sun, Wen-Chang; Zhang, Yun-Long; Lin, Qiu-Yue; Liao, Jia-Wei; Song, Gui-Rong; Ma, Xiao-Lei; Li, Hui-Hua; Zhang, Bo (Frontiers in Cell and Developmental Biology, 2021)
Pressure overload-induced hypertrophic remodeling is a critical pathological process leading to heart failure (HF). Suppressor of cytokine signaling-3 (SOCS3) has been demonstrated to protect against cardiac hypertrophy and dysfunction, but its mechanisms are largely unknown. Using primary cardiomyocytes and cardiac-specific SOCS3 knockout (SOCS3cko) or overexpression mice, we demonstrated that modulation of SOCS3 level influenced cardiomyocyte hypertrophy, apoptosis and cardiac dysfunction induced by hypertrophic stimuli. We found that glucose regulatory protein 78 (GRP78) was a direct target of SOCS3, and that overexpression of SOCS3 inhibited cardiomyocyte hypertrophy and apoptosis through promoting proteasomal degradation of GRP78, thereby inhibiting activation of endoplasmic reticulum (ER) stress and mitophagy in the heart. Thus, our results uncover SOCS3-GRP78-mediated ER stress as a novel mechanism in the transition from cardiac hypertrophy to HF induced by sustained pressure overload, and suggest that modulating this pathway may provide a new therapeutic approach for hypertrophic heart diseases.